Penerapan Metode Pembelajaran Fishbowl dalam Meningkatkan Keaktifan dan Hasil Belajar Siswa pada Mata Pelajaran Fiqih - Zuhrotul Mufidah; Nurul Azizah; Eko Saputra (MA'ALIM: Jurnal Pendidikan Islam, 2022)
This study aims to determine the application of the fishbowl method in increasing student activity and learning outcomes in fiqh subjects in class VIII A Pondok Pesantren Al-Madaniyah Jaro Kalimantan. The application of this method expecting to be a solution to overcome the problem of learning "outcomes, which," are still very low, it finding that 79% of students have not reached the KKM. This type of research is classroom action research using the Kemmis & Mc Taggart model. The results of this study "indicate" that the application of the fishbowl method can increase student learning activity. In the first cycle of students who are active 60%, while in the second cycle of students who are 100% active, the increase in cycles I and II are 40%. The increase in student learning outcomes in the first cycle of students who reached the KKM reached 65%, while in the second cycle students who achieved the KKM were 100% of the total number of students. So the increase in student learning outcomes in cycles I and II is 35%. Thus it can be said that the application of the fishbowl method can increase student activity and learning outcomes in Fiqh Lesson.